TLC Profile and Activity Test of Secondary Metabolites Aspergillus flavus âIn-Habitingâ Queen Termiteâs Nest Macrotermes gilvus on Enriched Media - Alen, Yohannes; Amelia, Rezki; Djamaan, Akmal (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Antibiotic are secondary metabolites yielded by microbe especially fungus. Previous research succesfull screened four kinds of fungus that live in termites queenâs nest, one of them was Aspergillus flavus. Furthermore, Alen et al (2016g) states that this fungus last to produce metabolite compounds on SDA media which only exist in first and secondÂ  subculture extract, omit gradually for the next culture. It was presumed happen caused a different habitat to grow. So it is necessary to enrich the media with queen termite nest to get back the initial metabolites. The enrichment was done using four different media concentrations (0.25; 0,50; 0.75 and 1 grams of nest/mL media). The results show that enrichment of 1 gram of nest/mL media provides the most optimum fungus growht. The thirdÂ subculture ofÂ AspergillusÂ flavusÂ is cultured on enriched media which will becomeÂ the fourth subculture, this fungus cultured until tenth subculture, do extractionÂ andÂ Â  fracination to each culture. Based on TLC profile analysis, the initial metabolite not yet formed until tenth subculture, but forms six new stain terpenoid compounds. Â The result of Â columns chromatography obtained 10Â sub-faction.Â Activity test was done by diffusion method to 12Â Â test bacteria andÂ 3Â testÂ fungus.Â Spot 2,5,6 (RfÂ 0.84; 0,36; 0,26) inhibit the growth of Pseudomonas aeruginosa ATCCÂ 27853, spot 3,4 (RfÂ 0.74; 0,52) inhibit the growth of MicrococcusÂ luteusÂ ATCCÂ 10240.Â The use of enriched media affect formation ofÂ  secondary metabolites AspergillusÂ flavus.Â Â Keyword : Secondary metabolites, Aspergillus flavus, Macrotermes gilvus Hagen., Enriched media, TLC Profiles, Activity Assay